Rahasia Tauhid dalam Surah al-Ikhlâś: Pendekatan Sufistik Syekh Abdul Qadir al-Jailani dalam Tafsir al-Jailani: Rahasia Tauhid dalam Surat al-Ikhlas: Pendekatan Sufistik oleh Syekh Abdul Qadir al-Jailani dalam Tafsir al-Jailani - Nahdhiah Nurul Islamiyah; Achmad Abu Bakar; Muhammad Irham; Syia’ul Haq; Serli Julita (IAIN Parepare, 2024)
This research explores the concept of tauhid in the interpretation of Surah Al-Ikhlas within Tafsir Al-Jailani by Sheikh Abdul Qadir Al-Jailani, using a Sufistic approach. Surah al-Ikhlâś is chosen for its profound emphasis on tauhid, a central teaching of Islam and a significant theme in Sufi tradition. The study aims to analyze how Sheikh Abdul Qadir Al-Jailani interprets Surah Al-Ikhlas and assess the relevance of his tafsir in the contemporary era. A library research method with a hermeneutic approach is employed to deeply examine the tafsir text and its interpretation of tauhid. This method connects the historical context of the tafsir with contemporary understandings. Primary sources include Tafsir Al-Jailani, supported by secondary literature to enrich the analysis. The findings reveal that Tafsir Al-Jailani highlights the esoteric dimensions of tauhid, particularly Allah’s absolute attribute of